Indium Doping of Lead-Free Perovskite Cs2SnI6 - Umedov, Shodruz T.; Grigorieva, Anastasia V.; Lepnev, Leonid S.; Knotko, Alexander V.; Nakabayashi, Koji; Ohkoshi, Shin-ichi; Shevelkov, Andrei V. (Frontiers in Chemistry, 2020)
Structure and properties of an inorganic perovskite Cs2SnI6 demonstrated its potential as a light-harvester or electron-hole transport material, however its optoelectronic properties are poorer than of lead-based perovskites. Here we report the way of light tuning of absorption and transport properties of cesium iodostannate(IV) Cs2SnI6 via partial heterovalent substitution of tin for indium. Light absorption and optical bandgaps of materials have been investigated by UV-vis absorption and photoluminescent spectroscopies. Low-temperature electron paramagnetic resonance spectroscopy was used to study the kind of paramagnetic centers in materials.